Literature Review: Hospital Managerial Characteristics impact in Health Workers - Krisnanda, Ariella (Universitas Muhammadiyah Surakarta, 2024)
Purpose: Hospital management is multidisciplinary which includes planning, organizing, coordinating, supervising, and controlling various resources to achieve hospital goals. Effective managerial characteristics can have a significant impact on the performance of health workers. This study will explore and analyze the current relevant literature on the managerial characteristics of hospitals and their relationship to the performance and satisfaction of health workers. Methodology: In this study, data was collected on Scopus through the PRISMA method. The results of this study obtained 117 appropriate and relevant documents. Results: Managerial characteristics such as managers in age, education, expertise, leadership, good communication and relationships with other workers affect the productivity and performance of health workers. Applications/Originality/Value: Good managerial characteristics, it can also create a good working environment and climate that improves the performance and satisfaction of health workers.